(untitled) (Baltic Journal of Sport and Health Sciences, 2025)
Background: Promoting healthy ageing is a major public health challenge, especially with increasing mild cognitive impairment (MCI) prevalence and associated dementia risk in older adults. Exercise training may improve cognitive function, yet studies on its effects in MCI populations remain limited and inconsistent in design and outcomes. This study investigated the impact of a 12-week structured lower limb resistance training (RT) programme on cognitive performance, specifically memory and executive function in older adults at low and high risk of MCI. Methods: Fifty-three older adults (aged 60–80) completed the study and were categorised into low risk (lrMCI, n = 28) and high risk (hrMCI, n = 25) MCI groups. Participants were assigned to a 12-week RT programme (2 sessions/week, 4 lower-limb exercises, 3 sets of 6–10 reps at 70–85% 1RM) or a passive control group. Cognitive performance was assessed using the Montreal Cognitive Assessment (MoCA) and ANAM4™ neurocognitive battery before and after the intervention. Results: At week 12, participants with high risk MCI in the resistance training group showed a significant improvement in MoCA total scores, particularly in executive function and delayed recall domains. An increase in MoCA scores was also observed in the control group, suggesting a potential learning effect. Performance across ANAM4 cognitive tasks did not show statistically significant changes following the intervention. Conclusion: A twice-weekly RT programme over 12 weeks did not produce robust improvements across all cognitive domains, but trends suggested potential benefits in executive function and inhibitory control among older adults at higher risk of MCI. The cognitive response to RT appears to vary by MCI risk level and baseline cognitive status. Keywords: older adults, MoCA (Montreal Cognitive Assessment), executive function, memory, ANAM4 neurocognitive battery